2008
DOI: 10.2478/v10033-008-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalization, Financial Development and Economic Growth in The Long Term: The Case of Turkey

Abstract: Abstract:T he determinants of economic growth have been a much debated theoretical issue in the literature, especially after the endogenous growth theory of the late 1 980s. T his new theory highlights the importance of economic policies that lead to an increasing rate of return. In particular, it is argued that human capital, trade liberalization and financial development may play very important roles in the determination of economic growth. T his paper tries to empirically estimate the joint impacts of trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 76 publications
3
11
0
1
Order By: Relevance
“…Further a 1% increase in FDI impedes growth in real GDP by 0.254% in Bangladesh. This result is consistent with the earlier findings of Hye (2011) for India but not with those found by Ang (2007); Khan and Qayyum (2007); Kar et al (2008), and Hye and Dolgopolova (2011) for Malaysia, Pakistan, Turkey, and China respectively, on average ceteris paribus. These authors found that a 1% increase in FDI increases economic growth by 0.096, 1.029, 0.015 and 0.25%, respectively.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Further a 1% increase in FDI impedes growth in real GDP by 0.254% in Bangladesh. This result is consistent with the earlier findings of Hye (2011) for India but not with those found by Ang (2007); Khan and Qayyum (2007); Kar et al (2008), and Hye and Dolgopolova (2011) for Malaysia, Pakistan, Turkey, and China respectively, on average ceteris paribus. These authors found that a 1% increase in FDI increases economic growth by 0.096, 1.029, 0.015 and 0.25%, respectively.…”
Section: Resultssupporting
confidence: 94%
“…Khan and Qayyum (2007) chose four indicators of financial development to construct FDI for Pakistan: total bank deposit liabilities; clearing house amount; private credit and the stock market capitalization, each as ratio of GDP. Kar et al (2008) used three proxies of financial development (M1/Y; M1/M2 and M2/Y) 11 for financial liberalization index for Turkey. Hye (2011) constructed financial development index for India by using four proxy indicators of financial development -market capitalization of listed companies, liquid liabilities and domestic credit to private sector as a percentage of GDP, and M2/M1.…”
Section: Construction Of Financial Development Indexmentioning
confidence: 99%
“…In case of financial development, a 1 percent increase in t lf drives the growth in real GDP by 0.039 percent, given that all else is same. This result is consistent with earlier findings reported by Ang, (2007); Khan and Qayyum, (2007) and Shahbaz, (2009Shahbaz, ( , 2012 and Kar et al (2008) for Malaysia, Pakistan and Turkey respectively. Capital usage has positive impact on economic growth as predicted by the growth theories.…”
Section: Resultssupporting
confidence: 93%
“…Moving to Nigeria, Chimobi (2010) In Turkey, Kar, Peker and Kaplan (2008) try to empirically estimate the joint impact of trade liberalization and financial development on economic growth. Instead of using common proxies for the issue, the principal components analysis is employed to develop better measures (indexes) for trade liberalization, financial development and the joint effect of both.…”
Section: Literature Reviewmentioning
confidence: 99%